Hobbits, Ents, and Pope Francis' "Laudato Si'": Environmental Echoes and Religious Resonances from J. R. R. Tolkien's "The Lord of the Rings" - Galang, Joseph Renus F. ca. 20./21. Jh. (Journal for the study of religion, nature and culture, 2025)
This paper describes how the environmental perspectives of Hobbits and Ents in J. R. R. Tolkien's The Lord of the Rings is echoed in and resonates with Pope Francis's teachings in Laudato Si'. The study also demonstrates how modern fantasy literature can be used as a resource to open dialogues regarding religious and theological ideas. Employing a narrative criticism of The Lord of the Rings trilogy and Laudato Si', this study finds that Tolkien and Francis stand on common ground regarding their environmental perspectives. While Francis discusses the cry of the earth, the gospel of creation and stewardship, a critique of the technocratic paradigm, and an integral ecology, Tolkien animated similar ideas through the figures of Hobbits and Ents and their interactions. Ultimately, both works leave in their readers with a profound sense of mission to implement change, recognizing that the shared home of all living beings is in great peril.